Dunkl-Poisson Equation and Related Equations in Superspace - Yuan, Hong Fen; Karachik, Valery V. (Mathematical Modelling and Analysis, 2015)
In this paper, we investigate the Almansi expansion for solutions of Dunkl-polyharmonic equations by the 0-normalized system for the Dunkl-Laplace operator in superspace. Moreover, applying the 0-normalized system, we construct solutions to the Dunkl-Helmholtz equation, the Dunkl-Poisson equation, and the inhomogeneous Dunkl-polyharmonic equation in superspace.